English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

y-1 / x +3 = - 3 / 4

2006-10-20 12:23:14 · 8 answers · asked by Anonymous in Science & Mathematics Mathematics

8 answers

I assume you mean solve the equation for y...

(y - 1) / (x + 3) = -3 / 4

Multiply both sides by (x + 3):
(y - 1) = -3/4 ( x + 3 )

Now add 1 to both sides:
y = -3/4 ( x + 3 ) + 1

Multiply the -3/4 through:
y = -3/4x + -9/4 + 1

Add the last two numbers (convert 1 to 4/4, if it helps):
y = -3/4x - 5/4

There's your equation solved for y (i.e. in y = mx + b format). Reading the values from the equation, the slope (m) is -3/4 and the y-intercept (b) is -5/4.

2006-10-20 12:30:11 · answer #1 · answered by Puzzling 7 · 0 0

this equation cannot be solved for x or y.
instead you might want to put it in the standard form of the equation of a line which is Y = mX + b where m is the slope and b is the y intercept
y-1 / x + 3 = -3 / 4 we cross multiply and get
4y - 4 = -3x -9 now we need to get y by itself on one side of the equation as seen in the standard from.
4y = -3x - 9 + 4
4y = -3x - 5
y = (-3x - 5) / 4 all of the (), the numerator is divided by 4
so we get
y = -3/4 x - 5 /4 so slope is -3 / 4 and y int is -5 / 4

2006-10-20 20:47:52 · answer #2 · answered by jamnad 1 · 0 0

y= (-3/4)x - (5/4)

2006-10-20 19:29:09 · answer #3 · answered by Nobody 3 · 0 0

for two variables you need two equations to get the absolute values
Otherwise you can solve for either y or x
Solution for y:
y-1/x+3 = -3/4, so 4(y-1) = -3(x+3), so 4y-4 = -3x-9, so 4y = -3x-5
so y = -3x/4-5/4
Solution for x:
from above 4y = -3x-5, so 3x = -4y-5, so x = -4y/3-5/3

2006-10-21 01:34:15 · answer #4 · answered by grandpa 4 · 0 0

You can't solve for both "x" and "y" without another equation. The only thing that you can do is simplify this formula into "y=mx+b" form. If you need help doing this, let me know and I'll edit my post.

2006-10-20 19:29:56 · answer #5 · answered by Josh 2 · 0 0

Perversity compels me to offer this answer:

-1/x = -(3/4)-3-y
1/x = y+(15/4)
y = (1/x) - (15/4)
y = (4-15x)/(4x)

2006-10-20 19:55:58 · answer #6 · answered by Helmut 7 · 0 0

4y-4=-3x-9

3x+4y+5=0
the equation cannot be solved
for solving for two variables we need two equations

2006-10-20 19:33:10 · answer #7 · answered by raj 7 · 0 0

y = -2
x = 1

2006-10-20 19:26:11 · answer #8 · answered by onlyafewwillknow 3 · 0 0

fedest.com, questions and answers